Facial hypertrichosis in the course of isotretinoin treatment: four-year retrospective observation - Pekmezci, Erkin (My University, 2024)
Background: isotretinoin is a synthetic retinoid used in the treatment of acne. There are limited and inconsistent data about the effects of isotretinoin on hormones and hair growth. Aim: to investigate a probable connection, a single center four-year retrospective data of female acne patients who were treated with oral isotretinoin and developed facial hypertrichosis was reported. Methods: in the years 2019-2023, 327 female patients between 16-33 years of age (Mean ± Standard Deviation: 23.4 ± 4.7) were treated with 0.5-0.8 mg/kg/day isotretinoin, approximately for 6 months (6.2 ± 0.8). The patients who developed facial hypertrichosis were additionally analysed for dehydroepiandrosterone sulfate, prolactin and thyroid stimulating hormone values. Results: thirty one patients (9.5%) in all ages (22.9 ± 4.3) declared excessive hair growth on cheeks and/or chin during treatment. All declarations were between the 2nd and 4th months (2.6 ± 0.8). The mean values of analysed hormones were in normal ranges. Twenty seven of the thirty one patients (87%) stated that the excessive hair growth terminated completely at the end of 4th month (3.1 ± 0.7) after the cessation of the treatment, and the others declared it was diminished to a great extent. Conclusions: mainly due to normal mean values of the analysed hormones, it is hard to consider that the cause of hypertrichosis is hormonal irregularity. However, 9.5% is a considerable ratio. A more extensive prospective study should be performed to reveal the cause of this phenomenon.
Keywords: Facial Hypertrichosis; Hirsutism; Isotretinoin